2002
DOI: 10.1159/000064006
|View full text |Cite
|
Sign up to set email alerts
|

Serial Evaluation of High-Resolution Computed Tomography Findings in Patients with Idiopathic Pulmonary Fibrosis in Usual Interstitial Pneumonia

Abstract: Background: The development of well-matured fibrosis in usual interstitial pneumonia (UIP) is strongly associated with an unfavorable outcome of patients with idiopathic pulmonary fibrosis (IPF). However, differences in the rates of development are likely to result in variable clinical courses in IPF patients. Objective: We tried to evaluate the progression of honeycombing and ground-glass opacity on CT using a scoring system, and to examine those serial changes in the clinical course of disease. Methods: A ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…30,33 Th e extent of honeycombing and of pulmonary fi brosis on CT scan has adverse prognostic ramifi cations. [33][34][35][36][37] Th ough we hoped to see a relationship between CT scan honeycombing and microscopic honeycombing, there was no such association in our study suggesting that honeycombing on CT scan and histology are dissimilar. It has been shown that CT scan honeycombing is associated with a poor prognosis but this is not the case for microscopic honeycombing; microscopic honeycombing also is not necessarily specifi c for a UIP diagnosis as opposed to CT scan honeycombing which is highly specifi c for UIP.…”
Section: Discussionmentioning
confidence: 99%
“…30,33 Th e extent of honeycombing and of pulmonary fi brosis on CT scan has adverse prognostic ramifi cations. [33][34][35][36][37] Th ough we hoped to see a relationship between CT scan honeycombing and microscopic honeycombing, there was no such association in our study suggesting that honeycombing on CT scan and histology are dissimilar. It has been shown that CT scan honeycombing is associated with a poor prognosis but this is not the case for microscopic honeycombing; microscopic honeycombing also is not necessarily specifi c for a UIP diagnosis as opposed to CT scan honeycombing which is highly specifi c for UIP.…”
Section: Discussionmentioning
confidence: 99%
“…There remains considerable error using combined clinical diagnostic criteria or even high-resolution CT scans with the accuracy of these methods hovering in the 70% range [11, 12]. Some have advocated the use of serial high-resolution CT scans in monitoring these patients, being able to better document increasing honeycomb changes or fibrosis in those with progressive disease [13]. However, the utility of this information in those with clinically progressive disease remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations have confirmed the concordance of HRCT images with physiologic, pathologic, and clinical manifestations of UIP [34]. Indeed, scoring of the honeycombing and tracking serial changes by HRCT has been shown to be useful for predicting the prognosis in patients with UIP [35]. To our knowledge, the current findings reveal how this evolving body of evidence is synthesized by chest clinicians and applied to their care of patients.…”
Section: Discussionmentioning
confidence: 54%